Utilization of interactive multimedia in learning english about different kinds of fruits for elementary school children - Anyan; Merla Madjid; Desty Endrawati Subroto; Arifin; Agus Rofi'i (Institute of Computer Science (IOCS), 2023)
English language lesson in elementary schools plays a crucial role in the development of children's English language and critical thinking abilities, as well as their creativity and self-assurance. The teaching and learning process at school or online now heavily depends on technology, including digital learning media that continue to expand and supplant traditional media such as books. Using interactive multimedia is one way to improve the efficacy of English learning, so the purpose of this study is to develop learning media with English material for the introduction of fruit vocabulary for elementary school students, which will facilitate the delivery and absorption of learning materials. To attract the attention of elementary school pupils, the interactive multimedia development method employs the Model Development Life Cycle (MDLC) with a minimalist and straightforward concept. The overall test results indicate that interactive multimedia learning English, particularly material about fruits, can be an option for students and instructors to support learning at school, and that the composition of the material is consistent with the school's curriculum. Having access to alternative learning media enables elementary school students to learn independently, enhance their skills, and meet school learning objectives.